Techno-economic and life cycle assessment of a novel offshore macroalgae biorefinery - Greene, Jonah M., author; Quinn, Jason C., advisor; Baker, Daniel, committee member; Petro, John, committee member (Colorado State University. Libraries, 2019)
Innovative and effective solutions to providing renewable fuels represent a critical need. The cultivation and conversion of salt water macroalgae into liquid transportation fuels may offer a viable alternative to petroleum-based diesel, but the potential of this technology in terms of economic feasibility and environmental impact has not been thoroughly investigated. This work evaluates the sustainability of a free-floating macroalgae cultivation to fuel concept. While free-floating biomass cultivation structures may offer solutions for reducing infrastructure requirements and expenses, extreme ocean conditions pose great risks and unknowns. This study focuses on emerging technologies for large scale cultivation and harvesting of macroalgae biomass including drone assisted seeding and harvesting operations, recycled carbon fiber long-lines with sensor equipped buoys, and adhesive spore seeding methods. The harvested biomass is then converted to fuels through hydrothermal liquefaction. Three different system pathways have been explored to determine the impacts of the various emerging technologies on the sustainability of the system and provide direction for future research and development. Results from the techno-economic analysis show a baseline minimum fuel selling price of $6.38 per Gallon of Gasoline Equivalent (GGE) with a range from $5.10 GGE-1 to $11.00 GGE-1 based on optimistic and conservative assumptions regarding biomass yield, length of the growing season, and technology readiness level. The 90% confidence interval from the Monte Carlo Analysis performed by varying the top 10 high-impact parameters, suggests a range of $6.02 GGE-1 to $11.17 GGE-1 for the baseline pathway. The well-to-wheel life cycle assessment (LCA) shows net greenhouse gas emissions of 22 gCO2-eq MJ-1 for the baseline pathway and a range of 18 to 32 gCO2-eq MJ-1 for the optimistic and conservative pathways, respectively. The Monte Carlo LCA results show a range of 19 to 27 g CO2-eq MJ-1 based on the 90% confidence interval. Discussion focuses on the feasibility of the various technologies and utilizes results from the analysis to weigh the risks and rewards associated with the proposed concept, in an effort to guide research and development for macroalgal cultivation and conversion systems.
Keywords: biorefinery; macroalgae; techno-economics; life cycle assessment; biofuels; offshore cultivation